2013
DOI: 10.18097/pbmc20135903330
|View full text |Cite
|
Sign up to set email alerts
|

Prooxidant and antioxidant activity of blood plasma and histology of internal organs of rats after intravenous administration of magnetite nanoparticles

Abstract: 1ГБОУ ВПО Сибирский государственный медицинский университет Минздравсоцразвития России, 634050, Томск, Московский тракт, 2; эл. почта: milto_bio@mail.ru 2 ФГБОУ ВПО Национальный исследовательский Томский политехнический университет, Томск 3 Обособленное структурное подразделение "Научно-исследовательский институт биологии и биофизики Томского государственного университета", ТомскМетодом люминол-зависимой хемилюминесценции исследовано влияние однократного и многократного внутривенного введения суспензии нанораз… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Evaluation of the antioxidant activity of NPs was considered as their potentially important toxic property (Karunakaran et al, 2013). Milto et al (2013) found that magnetite NPs exerted dose-dependent pro-oxidant and antioxidant properties in rat blood cells. In accordance to this in vivo finding, we observed that magnetite at concentrations of 5 and 10 mg/L led to increases in TAC levels in human blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the antioxidant activity of NPs was considered as their potentially important toxic property (Karunakaran et al, 2013). Milto et al (2013) found that magnetite NPs exerted dose-dependent pro-oxidant and antioxidant properties in rat blood cells. In accordance to this in vivo finding, we observed that magnetite at concentrations of 5 and 10 mg/L led to increases in TAC levels in human blood cells.…”
Section: Discussionmentioning
confidence: 99%